Implementing Problem-Based Learning (PBL) in social science courses: A case study on International relations - Balakrishnan, K.S. (2002)

(untitled)
Most of the disciplines within the social sciences have been mainly centred around textual analysis. The teaching processes are also lecturer centred with long hours of one way monologue. International relations and strategic studies is no exception in that. The traditional pedagogical approaches are prevalent. In a world where education and knowledge-seeking has been comercialised by global capitalism, the tendency to reexamine the traditional methodology to suit market demands is indeed inevitable. At the end of the way, it boils down to some of the very basic question of humanity which include what it means if the current education system could not provide the very means of bread and butter. At lease one saint said that modem.education can be about producing a higher clerk that can be called as lawyer. This warrants some serious investigation. Perhaps PBL could be only a beginning.